Benevolent leadership enhances organizational learning through communication, trust, and knowledge sharing - Salman Iqbal; Sami Ullah; Marek Zanker; Fatima Zainab (Scientific Reports)
Abstract This research addresses a significant gap in existing literature, which predominantly focuses on mainstream leadership styles, like transactional or transformational leadership. It illustrates how benevolent leadership, characterized by warmth and a paternalistic approach, can foster environments conducive to knowledge sharing and organizational learning. Utilizing a survey of 350 respondents from various knowledge-intensive organizations, the study employs structural equation modelling to analyze the data. The findings challenge the conventional belief that benevolent leadership inherently promotes a learning environment, suggesting that its effectiveness is significantly amplified when combined with trust and open communication. This study contributes to theoretical advancements by integrating social exchange theory with organizational learning, highlighting that the reciprocity triggered by benevolent leadership encourages employees to engage in positive knowledge-sharing behaviors, thereby enhancing organizational learning capabilities. For practitioners, these insights emphasize the importance of nurturing leadership styles that support trust and openness to foster a culture where knowledge is freely shared, thus enhancing the organization’s ability to adapt and innovate.